Utilização de hidrocolóides na estruturação de frutas tropicais: avaliação de aspectos tecnológicos, bioacessibilidade in vitro e perfil sensorial - Leal, Amanda Rodrigues (2017)
Structured fruits are products resulting from the combination of fruit pulps and gelling hydrocolloids, being an alternative for the reduction of fruit waste. In this context, the objective of the present study was to develop mixed structured fruits of mango with caja, mango with cashew apple and mango with acerola, evaluating the influence of the hydrocolloids on the sensorial, texture characteristics and on the retention of bioactive compounds. The mixed structured fruits were made combining fruit pulps with hydrocolloids ágar-ágar, low acyl gellan gum (LA) and high acyl gellan gum (HA), isolated or combined, in concentration of 0.75% of the weight of the pulps. It was evaluated the influence of hydrocolloids on sensory, physical-chemical and texture characteristics, as well as ascorbic acid content, polyphenols and total antioxidant activity, before and after gastrointestinal digestion in vitro. The results showed that pH and soluble solids of the structured fruits increased significantly compared to mixed pulps, while values of water activity remained unchanged, and it was observed a small variation in the coloration. Samples containing 100% ágar-ágar, 100% LA gellan gum with 0% gellan gum HA (LA100 / HA0), 75% LA gellan with 25% HA gellan (LA75 / HA25) and 50% LA gellan with 50% HA gellan (LA50 / HA50) presented physical-chemical characteristics very similar to each other. However, the structured fruits elaborated with ágar-ágar provided higher acidity, consequently, lower pH.The ascorbic acid contents of the structured fruits remained the same or, even, were higher than the content of the mixed pulps. There was a reduction of the polyphenols, except for the mango with acerola samples, whichthe maintenance of these components was observed. The antioxidant activity remained the same in the mango with caja and mango with acerola samples, and it was reduced in mango with cashew apple samples. The structured fruits maintained bioaccessible percentages of bioactive compounds similar to those found for the mixed pulps. In general, the structures fruits did not present differences in relation to the bioactive components comparing to each other. The samples containing ágar-ágar presented lower hardness than samples containing gellan gum, and LA100 / HA0 formulation was harder than the others. Otherwise, the adhesiveness was higher in LA100 / HA0, and this parameter reduced as the HA proportionincreased. The values of elasticity and cohesiveness were the same in all formulations. The structured fruits or mixed pulpsdid not present growth of microorganisms. All formulations were well accepted in the sensory evaluation, with higher preference for samples containing LA50 / HA50 and less preference for LA100 / HA0 samples. In view of the above, it is believed that the structured fruits presented in this study are very promising, because they present characteristics very similar comparing with mixed fruit pulps.